2021
DOI: 10.1200/op.20.00894
|View full text |Cite
|
Sign up to set email alerts
|

Dana-Farber Cancer Institute/Mass General Brigham Fellowship Response to the COVID-19 Pandemic

Abstract: The coronavirus disease (COVID)-19 pandemic has affected graduate medical education training programs, including hematology-oncology fellowship programs, both across the United States and abroad. Within the Dana-Farber Cancer Institute/Mass General Brigham hematology-oncology fellowship program, fellowship leadership had to quickly reorganize the program's clinical, educational, and research structure to minimize the risk of COVID-19 spread to our patients and staff, allow fellows to assist in the care of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…18,19 Both oncology and nononcology GME programs have reported adopting the use of virtual platforms for trainees' clinical and educational activities. 4,5,20-22 However, our findings highlight HO PD concerns regarding how to modify the evaluation and supervision of trainees to the virtual environment. PDs identified the lack of standardized practices and established guidance on virtual evaluation and supervision and suggested national societies could provide guidance on best practices for telehealth use and create environments for sharing experiences among PDs.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…18,19 Both oncology and nononcology GME programs have reported adopting the use of virtual platforms for trainees' clinical and educational activities. 4,5,20-22 However, our findings highlight HO PD concerns regarding how to modify the evaluation and supervision of trainees to the virtual environment. PDs identified the lack of standardized practices and established guidance on virtual evaluation and supervision and suggested national societies could provide guidance on best practices for telehealth use and create environments for sharing experiences among PDs.…”
Section: Discussionmentioning
confidence: 75%
“…3 Out of necessity, many HO fellowships and divisions implemented changes to their clinical, educational, and research environments. [4][5][6][7][8] However, the impact of COVID-19 on HO fellowship programs and PDs across the nation has not yet been rigorously characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found positive responses to virtual learning among trainees, including a survey of first-year HO fellows at Dana Farber Cancer Institute, which found higher attendance rates and more interactive sessions with virtual conferences compared with in-person lectures. 27 Similarly, the majority of HO fellows at MD Anderson felt that an online-based lecture program was as effective as in-person learning and considerably more flexible. 28 However, not all training programs were able to transition seamlessly to virtual learning.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Institutions have reported on efforts to improve the experience of HO fellows during the pandemic. 27 Because of the surge in Boston, Dana Farber fellows were pulled from various outpatient rotations to cover COVID-19–related services. However, fellows were rotated 4 days on and at least 4 days off to distribute the work more evenly, and COVID-19–related updates were given to fellows on a weekly basis, which was well received among first-year fellows.…”
Section: Discussionmentioning
confidence: 99%